Numerical studies using staggered finite volume for dam break flow with an obstacle through different geometries - Ikha Magdalena (Results in Applied Mathematics, 2021)
This paper aims to present a numerical study of dam break flow in the presence of an obstacle. A model based on the modified Non-Linear Shallow Water Equations with cross section and a dispersive treatment was solved numerically using a momentum-conservative finite volume method on a staggered grid. To validate the numerical model, several benchmark tests were carried out. Comparison of the computed results with the analytical and experimental data shows that the numerical model here proposed the flow with high accuracy. Moreover, the effect of the obstacle’s dimensions on the water height was examined. The extension to different contraction geometries of the simulation channel was examined.